Systematic Review on Association of Various Disease with Covid-19 - Prakash, Jay; Lodha, Shivani (Journal for Research in Applied Sciences and Biotechnology, 2024)
The SARS-CoV-2 virus, which causes COVID-19, initially emerged in Wuhan City, Hubei Province, China, in early December 2019. On January 30, 2020, the World Health Organisation proclaimed the pandemic a Public Health Emergency of International Concern. There have been 49,053 confirmed cases and 1,381 fatalities globally as of February 14, 2020. The risk of developing severe COVID-19 is increased in some congenital disorders, according to reported studies, because these conditions often come with pre-existing co-morbidities that impact the circulatory and respiratory systems, leading to potentially life-threatening pneumonia. A high risk for severe COVID-19 infection is not associated with congenital disorders other than those listed, even though they cause psychological discomfort in patients. A higher risk of developing new-onset diabetes among survivors was associated with COVID-19, according to this review. Glucose dysregulation must be closely monitored throughout the recovery process from SARS-CoV-2 infection. The SARS-CoV-2 virus has unleashed a COVID-19 pandemic that rivals the size of the 1918 flu pandemic. Although respiratory symptoms predominate, neurological symptoms are also being more acknowledged as a possible clinical manifestation. It is expected that SARS-CoV-2 will create many issues impacting the central nervous system or peripheral nervous system, based on what is known about previous coronaviruses like the ones that caused SARS and the Middle East respiratory syndrome outbreaks. Diabetes mellitus and arterial hypertension are risk factors for cardiovascular disease; the impact of COVID-19 on these conditions may not be fully recognised. Recent research suggests that a family history of COVID-19 infection may raise the risk of various cardiovascular diseases to a level comparable to those of established risk factors for this condition. Furthermore, the risk of developing CVD and the severity of its symptoms are both increased in patients with a preexisting condition, such as myocarditis, acute coronary syndrome, heart failure (HF), thromboembolic consequences, or arrhythmias. Direct viral penetration into cardiovascular tissue and activation of a robust systemic inflammatory response are two hypothesised methods by which COVID-19 may influence CVD and CV risk.